IMPLEMENTASI KEBIJAKAN PEMBELAJARAN TATAP MUKA DI PESANTREN DARUL MUSTOFA CIPANAS LEBAK BANTEN PADA MASA DARURAT COVID-19 - Wawan Abdullah (Karimiyah: Journal of Islamic Literature and Muslim Society, 2023)
One more year of pandemic covid-19 hit the world and impacted on the worl of education including boarding schools. Policies related to learning during the covid-19 pandemic made by the government behind Pesantren Darul Mustofa in education policy making in boarding schools. The purpose of this study is to describe the government’s policy in organizing education in Pesantren Darul Mustofa during the covid-19 pandemic. The research method that the authors use qualitative research is descriptive. Researchers describe an object, phenomenon, or social setting that will be reported in narrative writing. Data colletion techniques are carried out using triangulation techniques that are data disclosures made to data soureces. This technique is done by combining interview, and observation. The results showed that Pesantren Darul Mustofa has impemented health protocols that refer to government policies on the provisions and guidelines for organizing face-to-face learning in boarding schools